Memorandum on Five Year Plan [Development Aspects of Greater Bombay] - Planning Commission (Planning Commission)
The population of Greater Bombay which was 18 lakhs in 1941 has increased to 42 lakhs in 1961 and it is likely to rise to 71 lakhs in 1981. The people residing the Metropolitan area have naturally been expecting and demanding more amenities, but lack of funds particularly long term finance on easy terms has prevented the Corporation from providing more amenities as well as from undertaking any new activities commensurate with the requirements. To meet the needs of the growing population it is considered necessary to undertake extensive planning for improvement and expansion of the existing services as well as providing more amenities.
Municipal Corporation of Greater Bombay